2015
DOI: 10.1007/s10071-015-0833-9
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for memory interference across sessions in food hoarding marsh tits Poecile palustris under laboratory conditions

Abstract: Scatter hoarding birds are known for their accurate spatial memory. In a previous experiment, we tested the retrieval accuracy in marsh tits in a typical laboratory set-up for this species. We also tested the performance of humans in this experimental set-up. Somewhat unexpectedly, humans performed much better than marsh tits. In the first five attempts, humans relocated almost 90 % of the caches they had hidden 5 h earlier. Marsh tits only relocated 25 % in the first five attempts and just above 40 % in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…The initial argument (Clayton & Krebs 1994) was that non-caching species might remember both rewarded and non-rewarded locations equally well, resulting in higher memory load and hence higher proactive interference, while food-caching species were suggested to form strong memories specifically of rewarded locations, resulting in less proactive interference. Direct tests of this hypothesis found equivocal results (Hampton & Shettleworth 1996;Hampton et al 1998;Urhan & Brodin 2015). For example, Hampton et al (1998) reported more proactive interference in a food-caching species, which was associated with better memory of previous locations, just as in our study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The initial argument (Clayton & Krebs 1994) was that non-caching species might remember both rewarded and non-rewarded locations equally well, resulting in higher memory load and hence higher proactive interference, while food-caching species were suggested to form strong memories specifically of rewarded locations, resulting in less proactive interference. Direct tests of this hypothesis found equivocal results (Hampton & Shettleworth 1996;Hampton et al 1998;Urhan & Brodin 2015). For example, Hampton et al (1998) reported more proactive interference in a food-caching species, which was associated with better memory of previous locations, just as in our study.…”
Section: Discussioncontrasting
confidence: 63%
“…Highly specialized Clark's nutcrackers (Nucifraga columbiana) have also been shown to exhibit proactive interference (Lewis & Kamil 2006). Urhan and Brodin (2015) failed to detect proactive interference in marsh tits (Poecile palustris). In their paradigm birds recovered their food caches at each trial and did not need to remember specific rewarding locations in subsequent trials.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we have tested marsh tits in various food-hoarding experiments before in the same laboratory (Brodin and Urhan 2013; Urhan and Brodin 2015) and, during these experiments, marsh tits were highly motivated to both store and retrieve food. Moreover, they were able to memorise positions of their own caches.…”
Section: Discussionmentioning
confidence: 99%
“…However, songbirds occasionally swallow hemp achenes whole without cracking them [24,[28][29][30]. Some species temporarily hold hemp achenes in their beaks, and scatterhoard the achenes in hiding places -documented observationally [31][32][33] and in experimental studies [34,35].…”
Section: Cannabis Dispersal Mechanismsmentioning
confidence: 99%